Предмет: Алгебра,
автор: svetlanaburenok
Упростите выражение: 1)(5√3-√18)*√2
2) (√7+√6)^2
Ответы
Автор ответа:
0
1. ![(5 sqrt{3}- sqrt{18} ) sqrt{2}=5 sqrt{3} sqrt{2}- sqrt{18} sqrt{2}=5 sqrt{6}-6 (5 sqrt{3}- sqrt{18} ) sqrt{2}=5 sqrt{3} sqrt{2}- sqrt{18} sqrt{2}=5 sqrt{6}-6](https://tex.z-dn.net/?f=%285+sqrt%7B3%7D-+sqrt%7B18%7D+%29+sqrt%7B2%7D%3D5+sqrt%7B3%7D+sqrt%7B2%7D-+sqrt%7B18%7D+sqrt%7B2%7D%3D5+sqrt%7B6%7D-6+++++)
2/
2/
Автор ответа:
0
Спасибо))У меня так же все,но хотела проверить ссебя)))
Похожие вопросы
Предмет: Информатика,
автор: daiteban
Предмет: Биология,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Геометрия,
автор: GROMERisk
Предмет: Алгебра,
автор: gunel12